Comparison of the Effects of Different Cryoprotectants on Stem Cells from Umbilical Cord Blood - Gecai Chen; Aihuan Yue; Zhongbao Ruan; Yigang Yin; Ruzhu Wang; Yin Ren; Li Zhu (Stem Cells International)
Purpose. Cryoprotectants (CPA) for stem cells from umbilical cord blood (UCB) have been widely developed based on empirical evidence, but there is no consensus on a standard protocol of preservation of the UCB cells. Methods. In this study, UCB from 115 donors was collected. Each unit of UCB was divided into four equal parts and frozen in different kinds of cryoprotectant as follows: group A, 10% ethylene glycol and 2.0% dimethyl sulfoxide (DMSO) (v/v); group B, 10% DMSO and 2.0% dextran-40; group C, 2.5% DMSO (v/v) + 30 mmol/L trehalose; and group D, without CPA. Results. CD34+, cell viability, colony forming units (CFUs), and cell apoptosis of pre- and postcryopreservation using three cryoprotectants were analyzed. After thawing, significant differences in CD34+ count, CFUs, cell apoptosis, and cell viability were observed among the four groups (P<0.05).  Conclusion. The low concentration of DMSO with the addition of trehalose might improve the cryopreservation outcome.